PENERAPAN PROTOKOL PUBLISH / SUBSCRIBE MESSAGING SYSTEM PADA SISTEM WIRELESS BUILDING NETWORK BERBASIS NRF24L01 - Sarosa Castrena Abadi; Anton Prafanto; Mindit Eriyadi; Aris Suryadi; Givy Devira Ramadi (P3M Politeknik Negeri Indramayu, 2020)
Wireless sensor network is a common method used in the design of shared resource interconnection infrastructure at a location point to provide optimal performance. The main factor in the design of a wireless sensor network (WSN) communication protocol in the form of coordination optimization efforts between nodes, one of the effective methods that can be made to achieve such conditions is the provision of nodes using the publish / subscribe messaging system protocol. This research discusses the implementation of publish / subscribe messaging system protocol on wireless building network system based on NRF2L01. Discussions include simulation, design, implementation, application testing and system performance both on a work-to-work and performance-by-node performance. The results showed the system was able to monitor all information and control equipment from a building through a web interface making it easier for officers to maintain and supervise a building, then to test the performance of nodes with a fixed data packet size of 32 bytes, the delay value for each node is less than 1 second, then for the minimum throughput 250 kbps data rate obtained at 5.9 Kbps and the maximum throughput obtained at 72 Kbps and for packet loss of at least 0.59% while the maximum packet loss of 13.23% and the standard deviation value of delay, throughput and packet loss are smaller than the average value, the data is not very varied (stable).